Jolene - Lackey, Mercedes (Lackey, Mercedes. Elemental masters, 2021)
Learning elemental magic from her witch aunt after her Tennessee coal miner father's black-lung death, Anna May falls in love with a stonemason who abandons his work as a gravestone cutter to pursue true art.